Prognostic role of GPER/Ezrin in triple-negative breast cancer is associated with menopausal status. Issue 6 (June 2019) - Ye, Shuang; Xu, Yuanyuan; Li, Jiehao; Zheng, Shuhui; Sun, Peng; Wang, Tinghuai
Abstract : The role of G protein-coupled estrogen receptor 1 (GPER) signaling, including promotion of Ezrin phosphorylation (which could be activated by estrogen), has not yet been clearly identified in triple-negative breast cancer (TNBC). This study aimed to evaluate the prognostic value of GPER and Ezrin in TNBC patients. Clinicopathologic features including age, menopausal status, tumor size, nuclear grade, lymph node metastasis, AJCC TNM stage, and ER, PR and HER-2 expression were evaluated from 249 TNBC cases. Immunohistochemical staining of GPER and Ezrin was performed on TNBC pathological sections. Kaplan–Meier analyses, as well as logistic regressive and Cox regression model tests were applied to evaluate the prognostic significance between different subgroups. Compared to the GPER-low group, the GPER-high group exhibited higher TNM staging ( P  = 0.021), more death ( P  < 0.001), relapse ( P  < 0.001) and distant events ( P  < 0.001). Kaplan–Meier analysis showed that GPER-high patients had a decreased OS ( P  < 0.001), PFS ( P  < 0.001), LRFS ( P  < 0.001) and DDFS ( P  < 0.001) than GPER-low patients. However, these differences in prognosis were not statistically significant in post-menopausal patients (OS, P  = 0.8617; PFS, P  = 0.1905; LRFS, P  = 0.4378; DDFS, P  = 0.2538). There was a significant positive correlation between GPER and Ezrin expression level ( R  = 0.508, P  < 0.001) and the effect of Ezrin on survival prognosis corresponded with GPER. Moreover, a multivariable analysis confirmed that GPER and Ezrin level were both significantly associated with poor DDFS (HR: 0.346, 95% CI 0.182–0.658, P  = 0.001; HR: 0.320, 95% CI 0.162–0.631, P  = 0.001). Thus, overexpression of GPER and Ezrin may contribute to aggressive behavior and indicate unfavorable prognosis in TNBC; this may correspond to an individual's estrogen levels.